2019
DOI: 10.2147/hiv.s204661
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevention of mother-to-child transmission (PMTCT) of HIV: a review of the achievements and challenges in Burkina-Faso</p>

Abstract: Background Burkina-Faso’s HIV/AIDS program is one of the most successful in Africa, with a declining HIV prevalence and treatment outcomes that rival those of developed countries. Prevention of mother-to-child transmission (PMTCT) guidelines in Burkina-Faso, initiated in the year 2000, were revised in 2004, 2006 and 2010. The guideline document has since undergone several stages of improvement, largely based on recommendations from WHO, with adaptations by local experts in the field. Option B+ ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 83 publications
1
30
1
Order By: Relevance
“…If a baby is infected with HIV, they will receive the same care and treatment services as other HIV-positive patients for the rest of their lives. This program aims to reduce the rate of mother-to-child transmission, one of the goals of the HIV prevention and control program recommended to countries by WHO and UNAIDS [ 31 ]. This study confirms the effectiveness of PMTCT on early HIV diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…If a baby is infected with HIV, they will receive the same care and treatment services as other HIV-positive patients for the rest of their lives. This program aims to reduce the rate of mother-to-child transmission, one of the goals of the HIV prevention and control program recommended to countries by WHO and UNAIDS [ 31 ]. This study confirms the effectiveness of PMTCT on early HIV diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite effective therapies which have reduced the rate of mother-to-child HIV-1 transmission (45)(46)(47), approximately 150,000 infants were infected worldwide in 2019 (https://www.unaids.org/en/resources/fact-sheet). These children must be included in the larger quest for effective HIV-1 curative interventions, and such interventions may need to be tailored to their developing immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies worldwide showed that the adoption of Option B+ had contributed to a decrease in the rate of MTCT of HIV. 16,[25][26][27][28][29] During the 12-year follow-up of this cohort, of 229 women who were on ART before or during pregnancy, only one child (0.43%) whose mother received AZT monotherapy (Option A) had HIV-positive at the age of 18 months. This finding is consistent with the study of Kesho Bora Group; they found that the mothers who received AZT monotherapy were less effective in PMTCT than those receiving triple ARV.…”
Section: Discussionmentioning
confidence: 99%